Analysis the Effect of Midwife Assistance on Knowledge, Motivation, and Attitudes of Mothers to Care LBW Independently in Singosari Regional Health Center in Malang Regency - Yulida Tiani (Journal for Quality in Public Health, 2020)
Low birth weight (LBW) is a major cause of death in children under the age of 5 years. East Java has a prevalence of LBW higher than the national prevalence so reduce the prevalence of LBW is needed. The assistance of midwives to increasing maternal independence in treating LBW has the potential for reduce the mortality of LBW. The purpose of this study is to analyze the effect of midwives assistance on mothers' knowledge, motivation, and attitude to care for LBW independently in the Singosari public health center in Malang Regency, East Java. This study uses a quasi experimental control-group pretest-posttest research design and is taken using purposive sampling. Samples were mothers of LBW in the Singosari Regional Health Center in Malang Regency totaling 30 people. The sample was divided into two groups, each consisting of 15 mothers. In the intervention group, 4 visits were given assistance.The results of this study indicate that there are differences in the midwife assistance to the control group on the knowledge, motivation and attitudes of mothers in caring for LBW by value with p = 0.000, p=0.000 and p = 0.023 from the sig t independent.The midwives assistance increase the knowledge,motivation and attitudes of mother’s skill in terms of maintaining temperature, kangaroo methods, giving breast milk, preventing infection, and caring for the umbilical cord. Midwife assistance can be an alternative treatment for health workers to prepare mothers to care for LBW independently